Dynamics of phytohormones and their relationship with chalkiness of early indica rice under different post-anthesis temperature regimes (Bangladesh Journal of Agricultural Research, 2017)
A pot experiment on an early indica rice cv. Shenyou9576 was conducted in the net house of Hunan Agricultural University, Changsha, Hunan, PR China during the early growing season of 2013 to investigate the influence of varying temperatures on chalkiness rate, head rice rate, and phytohormones, namely indole-3-acetic acid (IAA), gibberellins (GA1 and GA4), zeatin (Z), zeatin riboside (ZR) and abscisic acid (ABA) both in flag leaves and grain endosperm during grain filling period. The treatments comprised three temperature regimes which are designated as the high (35/28oC- day/night), low (25/20oC- day/night) and natural condition as the control (35/25oC- day/night). The results showed that the maximum chalkiness rate was 61.11% under high temperature and the minimum (22.59%) under low temperature. The lowest head rice rate was 42.76% under high temperature followed by 49.91% in the control, while the highest (62.33%) under low temperature. The contents of GA1, GA4, Z and ZR were decreased gradually from 7 to 35 days after anthesis (DAA) irrespective of treatments. IAA content began to decrease from 14 DAA and continued up to 35 DAA and ABA was reduced from 28 to 35 DAA under low temperature in comparison to control and high temperature. ABA content was increased from 7 to 21 DAA and then declined at high temperature. The results showed that contents of GA1, GA4, Z, ZR were high at low temperature compared to high temperature and control. IAA content was also high during grain development period at low temperature except 7 DAA. Higher phytohormone contents were observed in endosperm than in flag leaves. Phytohormone content ratio (endosperm: flag leaves) was found highest in IAA and the lowest in GA1. A significant positive correlation was found between ABA and chalkiness rate during early to mid grain filling period, while significant negative correlations were noticed between chalkiness rate and other phytohormones during grain filling period. Correlation results revealed that increased level of ABA during early to mid grain filing period caused by high temperature was more responsible for development of chalkiness.Bangladesh J. Agril. Res. 42(1): 53-65, March 2017